Service utilisation by children with conduct disorders. - Vostanis P; Meltzer H; Goodman R; Ford T (European Child & Adolescent Psychiatry, 2003)
Background Children with conduct disorders and their families come into contact with a range of community and specialist agencies. Methods The aim of this study was to establish the lifetime service utilisation rates among children with conduct disorders from the Great Britain National Study (N = 10,438), and to examine the association between comorbid disorders, family and social factors, and service utilisation. The Development and Well-Being Assessment, a service checklist, and a battery of family and social functioning measures were used. Results The weighted prevalence of oppositional and conduct disorders was 5.4 %. Within this group (N =403), 241 (59.8%) had conduct disorder only 79 (19.6%) comorbid emotional, 72 (17.9%) comorbid hyperkinetic, and 11(2.7%) comorbid emotional and hyperkinetic disorders. These subgroups were compared on service utilisation with children with other psychiatric disorders (N=351). Children with conduct disorders had significantly higher lifetime rates of utilisation of social and educational services than children with other psychiatric disorders. Contact with primary health, specialist health, and educational services was significantly associated with comorbid physical and psychiatric disorders. In contrast, contact with social services was associated with family discord and social sector tenancy. Conclusions The findings are discussed in the context of organisation and coordination of health, other statutory, and non-statutory services, also taking into account previous research on interventions for children with conduct disorders and their families.